Cenicriviroc inhibits trans‐endothelial passage of monocytes and is associated with impaired E‐selectin expression. Issue 6 (8th August 2018) - D'Antoni, Michelle L.; Mitchell, Brooks I.; McCurdy, Sara; Byron, Mary Margaret; Ogata‐Arakaki, Debra; Chow, Dominic; Mehta, Nehal N.; Boisvert, William A.; Lefebvre, Eric; Shikuma, Cecilia M.; Ndhlovu, Lishomwa C.; Baumer, Yvonne
Abstract: Incidences of cardiovascular diseases (CVD) are high among virologically suppressed HIV‐infected individuals. Monocyte activation and trafficking are key mechanisms in the evolution of CVD. We studied the ability of cenicriviroc (CVC), a dual C‐C chemokine receptor type 2 (CCR2) and CCR5 antagonist, to influence the migration of monocytes from HIV‐infected individuals on antiretroviral therapy (ART). Monocytes were derived from 23 ART‐suppressed HIV‐infected and 16 HIV‐uninfected donors. In a trans‐endothelial migration model, monocytes, and human aortic endothelial cells (HAoECs) were exposed to cenicriviroc and migrated monocytes, quantified. Expression of CCR2 and CCR5 on monocytes and adhesion molecules (E‐selectin, ICAM‐1, VCAM‐1, PECAM‐1, and CD99) on HAoECs were measured. The single antagonists, BMS‐22 (CCR2), and maraviroc (CCR5), served as controls. When both HAoECs and monocytes together were exposed to the antagonists, cenicriviroc led to a greater decrease in monocyte migration compared to BMS‐22 or vehicle in both HIV‐infected and HIV‐uninfected groups ( P  < 0.05), with maraviroc having no inhibitory effect. Cenicriviroc treatment of HAoECs alone decreased monocyte migration in the HIV‐infected group when compared to vehicle ( P  < 0.01). Inhibition of migration was not evident when monocytes alone were exposed to cenicriviroc, BMS‐22 or maraviroc. Incubation of HAoECs with cenicriviroc decreased E‐selectin expression ( P  = 0.045) but had limited effects on the other adhesion molecules. Cenicriviroc inhibits monocyte trans‐endothelial migration more effectively than single chemokine receptor blockade, which may be mediated via disruption of monocyte‐endothelial tethering through reduced E‐selectin expression. Cenicriviroc should be considered as a therapeutic intervention to reduce detrimental monocyte trafficking. Abstract : Cenicriviroc, a dual CCR2 and CCR5 antagonist, inhibits monocyte trafficking in an in vitro trans‐endothelial migration assay more effectively than a single chemokine receptor blockade.